EP13 A standard case of reactive arthritis? Plot twist!. (20th April 2020) - DESAI, ANU; Justice, Elizabeth; Rahman, Mahjabeen; Johnson, Aimee
Abstract: Background: A 49 year old male patient presented to the acute medical unit with history of acute onset high grade fever with polyarthritis involving right knee, left elbow, both ankles and small joints of right hand preceded by 2 days of diarrhoea and vomiting. He had temperature of 38°C, BP: 156/77 mmHg, Pulse rate: 98/min. Initial blood tests: CRP: 312, ESR: 51, and leucocytosis (WBC count: 17.9 with neutrophilia: 13.1). The medical team considered diagnosis of multifocal septic arthritis and initiated IV flucloxacillin empirically. He had past medical history of recently treated extra pulmonary tuberculosis three months prior to admission. Methods: CT thorax abdomen and pelvis scan was organised to rule out reactivation of tuberculosis/Poncet's arthritis. CT revealed generalised lymphadenopathy and bilateral hip effusions. At this point, a Rheumatology opinion was requested, a synovial fluid aspiration from the right knee, the most affected joint, was performed. The turbid sample had numerous pus cells, but negative gram stain and negative cultures after prolonged culture. AFB stain was negative. He was improving systemically but had intermittent fevers and CRP remained high (155mg/l). Synovial fluid sample was sent for 16S PCR testing and Streptococcus pyogenes ribosomal DNA was detected. Testing for serum ASO titres revealed elevated titres (32000 IU/mL). In conjunction with microbiology team, we augmented antibiotics to IV Gentamicin and IV Ceftriaxone. A careful history revealed transient throat infection of 6 hours duration 10 days prior to onset of arthritis. Urinary dipstick and ACR revealed proteinuria (ACR 84.8). This is under close follow-up with renal team who feel that post Streptococcal Glomerular Nephritis is likely but deferred renal biopsy. 2 DECHO study ruled out valve abnormality. A right inguinal lymph node biopsy was attempted; however, tissue sample was unsuitable. Hepatitis screen was negative and Antibody panel (ANA, ANCA were negative, RF: borderline positive (26) were unremarkable. He received total duration of 31 days of antibiotics. CRP eventually improved to 13, on follow up, in view of persisting arthritis, orals steroids (15mg OD) was prescribed for three weeks. Results: Thus, we achieved a compelling diagnosis of acute rheumatic fever, with possible focus in the throat and probably bacteraemic spread to the right knee. PCR analysis of synovial fluid in context of negative culture guided antibiotic therapy choice, duration and cautious approach for immunosuppression. The patient's story evolved with development of proteinuria suggestive of possible post streptococcal glomerulonephritis which is under follow up. Conclusion: Rheumatologists are faced with challenge of reviewing ill patients with joint effusions in whom empirical antibiotics have been started. In this scenario, joint aspiration yields lower positive culture results. 16S PCR analysis can help in guiding antibiotic choice and duration with negative culture. Disclosures: A. Desai None. E. Justice None. M. Rahman None. A. Johnson None.